Endoscopic removal of over‐the‐scope clips: Clinical experience with a bipolar cutting device. Issue 4 (1st June 2017) - Bauder, Markus; Meier, Benjamin; Caca, Karel; Schmidt, Arthur
Abstract : Background: Over‐the‐scope clips (OTSCs) are increasingly used for the closure of perforations/fistulae, hemostasis and endoscopic full‐thickness resection (FTRD system). When OTSC‐associated complications occur or re‐therapy at the OTSC site is needed, OTSC removal may be indicated. An experimental study in an animal model and a case series have shown good results for OTSC removal with a bipolar cutting device. We present a larger clinical study using this device. Methods: Data of all consecutive patients with indication for OTSC removal were collected and analyzed retrospectively. OTSCs were cut at two opposing sites using a bipolar grasping device to apply short direct current impulses. OTSC fragments were extracted with a standard forceps and a cap at the tip of the endoscope to avoid tissue damage. Results: Between December 2012 and February 2016 a total of 42 OTSC removals in the upper ( n  = 25) and lower ( n  = 17) gastrointestinal tract have been performed at our department. Overall technical success, defined as cutting the OTSC at two opposing sites and extraction of both fragments, was achieved in 92.9% (39/42) of all cases. Successful fragmentation of the OTSC was achieved in 97.6% (41/42). Minor bleedings were rare and could be managed endoscopically in all cases. There were no perforations and no major or delayed bleedings. Conclusion: Endoscopic OTSC removal with a bipolar cutting device is feasible, effective and safe. This technique can be applied in the upper and lower gastrointestinal tract.